The Contribution of Microteaching Achievements and Teaching Readiness to Teaching Practicum Achievements in The Civil Engineering and Planning Education Study Program Faculty of Engineering Yogyakarta State University - Nur Izzi Sibiani; V Lilik Hariyanto; Aan Yudianto (Universitas Negeri Yogyakarta, 2024)
Background: The main purpose of this study was to determine the contribution of micro teaching achievements and teaching readiness to teaching practicum achievements in the Civil Engineering and Planning Education Study Program at Faculty of Engineering, Yogyakarta State University.Methods: This research is an ex-post facto study. The population of this study was 90 students of the Civil Engineering and Planning Education Study Program, class of 2019, with a sample of 73 students. The data collection technique used a questionnaire and documentation methods. Data analysis techniques were carried out using descriptive statistics, prerequisite analysis tests, and multiple regression analysis.Results: The results of the study show that: 1) there is a positive and significant effect of micro teaching achievements to teaching practicum achievements with tcount > ttable (2.480 >1.993943) at a significance level of 5%, 2) there is a positive and significant effect of teaching readiness to teaching practicum achievements with tcount > ttable (25.871 > 1.993943) at a significance level of 5%, 3) there is a positive and significant effect of micro teaching achievements and teaching readiness together to teaching practicum achievements with R2 = 0.966; Fcount > Ftable (1009.222 >3.12576424) at a significance level of 5%. The relative contribution of micro teaching achievements is 7.296% and the effective contribution is 7.05%. The relative contribution of teaching readiness is 92.704% and the effective contribution is 89.58%.Conclusion: There is a positive and significant influence of Micro Teaching Achievements and Teaching Readiness on Teaching Practicum Achievements in the Civil Engineering and Planning Education Study Program with a contribution of 96.63%.